2012
DOI: 10.1186/1471-2393-12-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lay Support in Pregnant women with Social risk (ELSIPS): a randomised controlled trial

Abstract: BackgroundMaternal, neonatal and child health outcomes are worse in families from black and ethnic minority groups and disadvantaged backgrounds. There is little evidence on whether lay support improves maternal and infant outcomes among women with complex social needs within a disadvantaged multi-ethnic population in the United Kingdom (UK).Method/DesignThe aim of this study is to evaluate a lay Pregnancy Outreach Worker (POW) service for nulliparous women identified as having social risk within a maternity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…One trial with multiple arms aimed to evaluate health system and community interventions separately and together (Morris 2004a ). Ten trials evaluated community interventions alone (Barber 2008 ; Fottrell 2013 ; Laken 1995 ; Lewycka 2013a ; Manandhar 2004 ; Melnikow 1997 ; More 2012 ; Mori 2015 ; Mullany 2007 ; Tripathy 2010 ). The rest of the trials (13) aimed to evaluate a combination of health system and community interventions (Azad 2010 ; Baqui 2008 ; Bhutta 2011 ; Kirkwood 2013 ; Klerman 2001 ; Kumar 2008 ; le Roux 2013 ; Midhet 2010 ; Omer 2008 ; Villar 1992 ; Wahlstrom 2011 ; Waiswa 2015 ; Wu 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…One trial with multiple arms aimed to evaluate health system and community interventions separately and together (Morris 2004a ). Ten trials evaluated community interventions alone (Barber 2008 ; Fottrell 2013 ; Laken 1995 ; Lewycka 2013a ; Manandhar 2004 ; Melnikow 1997 ; More 2012 ; Mori 2015 ; Mullany 2007 ; Tripathy 2010 ). The rest of the trials (13) aimed to evaluate a combination of health system and community interventions (Azad 2010 ; Baqui 2008 ; Bhutta 2011 ; Kirkwood 2013 ; Klerman 2001 ; Kumar 2008 ; le Roux 2013 ; Midhet 2010 ; Omer 2008 ; Villar 1992 ; Wahlstrom 2011 ; Waiswa 2015 ; Wu 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies show that group prenatal care and group prenatal education can provide multiple types of support 37 38. A randomised control trial of pregnancy outreach workers in the UK designed to provide tangible, emotional and informational support to vulnerable women showed a reduction in depressive symptoms 39. For areas where in-person support is not feasible, randomised clinical trials have shown that peer support interventions delivered over the phone or internet during the postnatal period can provide emotional and informational support and reduce depressive symptoms 36.…”
Section: Discussionmentioning
confidence: 99%
“…21 Prior to the trial, data was not available on numbers of social risk factors women had. Following a successful initial 6 months pilot where 475 women were recruited, it was observed that 64% had two or more social risk factors, and it was agreed to increase the sample size to allow power to detect differences in primary outcomes in the prespecified subgroup of women with two or more social risk factors, that is, so that the required sample size of 421 would be recruited within this subgroup.…”
Section: Sample Size Justificationmentioning
confidence: 99%